2020
DOI: 10.1039/c9dt02918d
|View full text |Cite
|
Sign up to set email alerts
|

Heterodinuclear complexes featuring Zn(ii) and M = Al(iii), Ga(iii) or In(iii) for cyclohexene oxide and CO2 copolymerisation

Abstract: A series of heterodinuclear zinc(ii)-Group 13 catalysts are synthesised by a sequential metalation procedure. They are active catalysts for the ring opening copolymerisation of cyclohexene oxide and CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 59 publications
0
32
1
Order By: Relevance
“…Over the last decade, a series of heterodinuclear metallic catalysts have emerged with excellent catalytic performance due to the synergetic effect between metal centers. Detailed kinetic, mechanistic, and theoretical studies suggest a "chain shuttling" mechanism where the rate-limiting step is metalcarbonate attack on a coordinated epoxide; thus, shuttle and activation of monomers at different metal centers can improve catalyst performance (Trott et al, 2019;Deacy et al, 2020a). Moreover, these studies demonstrated that heterodinuclear metal complexes may have better thermodynamic stability than the homodinuclear analogs (Deacy et al, 2018;Trott et al, 2019).…”
Section: Heterodinuclear Complex Catalystmentioning
confidence: 97%
See 2 more Smart Citations
“…Over the last decade, a series of heterodinuclear metallic catalysts have emerged with excellent catalytic performance due to the synergetic effect between metal centers. Detailed kinetic, mechanistic, and theoretical studies suggest a "chain shuttling" mechanism where the rate-limiting step is metalcarbonate attack on a coordinated epoxide; thus, shuttle and activation of monomers at different metal centers can improve catalyst performance (Trott et al, 2019;Deacy et al, 2020a). Moreover, these studies demonstrated that heterodinuclear metal complexes may have better thermodynamic stability than the homodinuclear analogs (Deacy et al, 2018;Trott et al, 2019).…”
Section: Heterodinuclear Complex Catalystmentioning
confidence: 97%
“…Since the metals from Group 1 or 2 are highly Lewis acidic, considering this feature may enhance the coordination of epoxides, and it is possible to generate unstable metal-carbonate bonds to lead a faster catalytic rate. A series of heterodinuclear combinations, featuring Zn(II)/M (Deacy et al, 2018(Deacy et al, , 2020a, were chelated by the macrocyclic ligand (Figure 7). For ROCOP of CHO/CO 2 , the most active and selective catalyst feature was Mg(II)/Zn(II), while all other heterodinuclear combinations showed a weaker activity.…”
Section: Heterodinuclear Complex Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a similar observation was made for another series of heterodinuclear catalysis for carbon dioxide/CHO ROCOP where a macrocyclic ancillary ligand was coordinated with Zn(II)M, where M = Li(I), Na(I), K(I), Ca(II), Al(III), Ga(III) and In(III); all combinations were less active than the di-Zn(II) catalyst. 35,38 Thus, the Zn(II)Mg(II) combination is somewhat special amongst the set of metals in providing heterodinuclear synergy. To target this desirable combination, attempts were made to prepare Zn(II)Mg(II) complexes from the precursors (3) and (8).…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…17,27 Furthermore, metals from groups 1, 2 and 12 are attractive targets due to their lack of colour, low toxicity and low cost. [35][36][37][38] Dinuclear catalysts based on both Zn(II) and Mg(II) are well known in the ROCOP of CO 2 /epoxide, [39][40][41] but are much less explored for the ROCOP of anhydride/epoxide ( Fig. S1IV and V †).…”
Section: Introductionmentioning
confidence: 99%